2023
DOI: 10.18063/som.v3i3.692
|View full text |Cite
|
Sign up to set email alerts
|

(Online First)Applying high-resolution visible imagery to satellite melt pond fraction retrieval: A neural network approach

Abstract: During summer, melt ponds have a significant influence on Arctic sea-ice albedo. The melt pond fraction (MPF) also has the ability to forecast the Arctic sea-ice in a certain period. It is important to retrieve accurate melt pond fraction (MPF) from satellite data for Arctic research. This paper proposes a satellite MPF retrieval model based on the multi-layer neural network, named MPF-NN. Our model uses multi-spectral satellite data as model input and MPF information from multi-site and multiperiod visible im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…method developed by . These findings are corroborated by Liu et al (2017) and Wright and Polashenski (2020), who concluded that machine learning could improve melt pond retrievals from MODIS over current spectral unmixing techniques. After the most traditional techniques for melt ponds studies, such as thresholding and spectral unmixing, ML started to be used for melt pond classifications, for both optical (e.g.…”
Section: Machine Learning-based Studiesmentioning
confidence: 52%
See 2 more Smart Citations
“…method developed by . These findings are corroborated by Liu et al (2017) and Wright and Polashenski (2020), who concluded that machine learning could improve melt pond retrievals from MODIS over current spectral unmixing techniques. After the most traditional techniques for melt ponds studies, such as thresholding and spectral unmixing, ML started to be used for melt pond classifications, for both optical (e.g.…”
Section: Machine Learning-based Studiesmentioning
confidence: 52%
“…There has been a growing number of studies applying machine learning-based approaches to MPF retrievals (e.g. Wright, 2020;Liu et al, 2017;Ding et al, 2020a;Feng et al, 2021;Peng et al, 2022). Wright (2020) proposed that the accuracy of the machine learning methods is better than that of the linear spectral unmixing due to the error caused by fixed reflectance feature (e.g.…”
Section: Machine Learning-based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ANN has been used to retrieve sea ice parameters (Rösel et al, 2012;Liu et al, 2017). It is shown that ANN has the potential to learn the complex relationship between sea ice parameters and input data.…”
Section: Methodsmentioning
confidence: 99%
“…In many regions, the difference of the averaged MPF between the MODIS retrieval and AMSR-E retrieval during 2002-2011 is less than 5% (Tanaka et al, 2016). More recently, Liu et al (2017) tested an alternative way for the MPF retrieval in summer 2008 by using artificial neural network (ANN). The visible imagery from the National Snow and Ice Data Center (NSIDC) are used as prior knowledge for the network training.…”
mentioning
confidence: 99%